Predictor of Organizational Performance: Examining Moderating Role of Social Media - Narintorn Somthong; Poonsak Sangsunt; Pipat Pichetsiraprapa; Mano Prachayapipat (International Journal of Supply Chain Management, 2020)
The basic purpose of the present study is to examine the impact of CSR activities of organization and organizational culture on organizational performance. Moreover, the mediating role of environmental supply chain performance along with moderating role of social media is examined as well. The data is collected from the customers of Fishery industry of Indonesia. In the form of survey questionnaires. The response rate of the current study is 47.3 percent. For analysis, PLS-SEM is employed. The findings of the study revealed that there exists significant relationship among all proposed independent variables and dependent variable. All of the proposed hypothesis was accepted except the relationship of social media on organizational performance was not accepted. The findings of the present study are important for the practitioners of supply chain and policy makers of fishery industry to derive the policy by which they can implement environmentally friendly supply chain performance through which the organizational performance can be improved